(untitled) (Journal of the College of Basic Education, 2025)
This research examines the topics addressed by Abu Abdullah Muhammad ibn Abi Bakr Al-Zuhri, who passed away in the mid-sixth century AH. His book is considered part of the Andalusian Islamic scholarly heritage. Early Arab writers recognized and referenced his work, citing excerpts and pages, as it contains significant historical information . Given this importance, I aim to provide an overview of the civilizational aspects of the Islamic Maghreb as highlighted by Al-Zuhri in his work. Andalusian geographers followed a unique methodological approach, laying the foundations of geographical thought. Al-Zuhri is regarded as a continuation of a series of geographers who were deeply invested in geographical scholarship. The term Geography originally means map, and its synonyms include safrah (journey) or mufradah (singular term), as frequently mentioned in his book with expressions like we depicted or we drew. Al-Zuhri composed his book based on earlier geographical works, his personal observations in Andalusian lands, and accounts from his contemporaries, some of whom he named. His references included prominent figures such as Al-Mas‘udi, Aristotle, Ibn Hayyan, and Al-‘Udhri. In Al-Zuhri’s view, geographical knowledge complemented historical studies. As he stated in his book, it encompassed all regions of the world, describing their inhabitants, appearances, morals, diets, and drinking habits, as well as the various resources, artifacts, perfumes, and luxuries each region produced. Additionally, he detailed the unique animals found across different parts of the world, noting their characteristics and toxic properties.